2013 18th International Conference on Digital Signal Processing (DSP) 2013
DOI: 10.1109/icdsp.2013.6622758
|View full text |Cite
|
Sign up to set email alerts
|

A non-iterative approach to frequency estimation of a complex exponential in noise by interpolation of fourier coefficients

Abstract: Abstract-In this paper a novel algorithm is presented for frequency estimation of a complex exponential by interpolating Fourier coefficients in a non-iterative way by shifting the minimum variance and using a non-linear function. The estimator presented is unbiased and normally distributed with asymptotic variance that is ≈ . of the Cramer RaoBound and is optimally uniform over the entire range while requiring calculation of the fewest Fourier coefficients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Numerous efforts have been made in the past to achieve fast and accurate frequency recovery through DFT interpolation. Existing solutions can be roughly divided into two categories: direct methods [11], [12], [13], [14], [15], [16], [17], [18] and iterative schemes [19], [20], [21], [22], [23], [24]. The former operate by reprocessing the maximum DFT coefficient and its neighbours that are available from the coarse search stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous efforts have been made in the past to achieve fast and accurate frequency recovery through DFT interpolation. Existing solutions can be roughly divided into two categories: direct methods [11], [12], [13], [14], [15], [16], [17], [18] and iterative schemes [19], [20], [21], [22], [23], [24]. The former operate by reprocessing the maximum DFT coefficient and its neighbours that are available from the coarse search stage.…”
Section: Introductionmentioning
confidence: 99%
“…Using the fixedpoint theorem, it is shown that both schemes converge after two iterations, thereby requiring four auxiliary DFT samples to complete the fine tuning stage. Methods to reduce the processing load without sacrificing the system performance are reported in [20], [21], and [22]. More recently, Fan and Qi [23] have proposed an iterative scheme (denoted as FQE) based on interpolation of three DFT coefficients, namely the central DFT peak and two auxiliary spectral lines with arbitrary shifts of ±qΔf .…”
Section: Introductionmentioning
confidence: 99%